Dissolution of cellulose with ionic liquid in pressurized cell - Ibrahim, F. (Elsevier, 2015)
In recent years, ionic liquids (ILs) have emerged as a potentially attractive "green" solvent for the dissolution of cellulose for further chemical processing. Generally, the dissolution of cellulose in ILs via a conventional heating system requires high temperature and long pretreatment time. This article investigates the effect of pressure on the dissolution of cellulose in IL emimOAc (1-ethyl-3-methylimidazolium acetate). The effects of dissolution temperature and dissolution pressure on cellulose dissolution time were investigated using High Pressure Solubility Measurement System (HPSMS). Â© 2015 Elsevier B.V. All rights reserved.